Functions of IgM fc receptor (FcµR) related to autoimmunity - Hiromi Kubagawa; Pedram Mahmoudi Aliabadi; Khlowd Al-Qaisi; Peter K. Jani; Kazuhito Honjo; Shozo Izui; Andreas Radbruch; Fritz Melchers (Taylor & Francis Group, 2024)
AbstractUnlike Fc receptors for switched immunoglobulin (Ig) isotypes, Fc receptor for IgM (FcµR) is selectively expressed by lymphocytes. The ablation of the FcµR gene in mice impairs B cell tolerance as evidenced by concomitant production of autoantibodies of IgM and IgG isotypes. In this essay, we reiterate the autoimmune phenotypes observed in mutant mice, ie IgM homeostasis, dysregulated humoral immune responses including autoantibodies, and Mott cell formation. We also propose the potential phenotypes in individuals with FCMR deficiency and the model for FcµR-mediated regulation of self-reactive B cells.